Identification of crucial areas of territorial ecological restoration based on ecological security pattern: A case study of the central Yunnan urban agglomeration, China - Yuju Ran; Dongmei Lei; Jie Li; Liping Gao; Jinxiao Mo; Xuan Liu (Ecological Indicators, 2022)
Territorial ecological restoration is an important measure of China’s ecological civilization construction strategy. However, one of the difficulties in the current land space planning is to scientifically determine the crucial areas of territorial ecological restoration. Taking the central Yunnan urban agglomeration as a case, from the perspective of ecosystem service supply (ESS) and ecosystem service demand (ESD), this study proposed a scientific solution to construct ecological security pattern (ESP) and identify the crucial areas of territorial ecological restoration at the scale of urban agglomeration. The results showed that: (1) The ESS and the ESD had significant diversity in their spatial distribution pattern. The high-value areas of ESS were primarily located in the west, whereas the high-value areas of ESD were primarily located in the middle. (2) The ESP was composed of 2 kinds of sources and 3 kinds of corridors. In details, the area of ecological sources and urban sources was 3.04 × 104 km2 and 2.60 × 103 km2, respectively, and the total length of river ecological corridors, potential ecological corridors and demand corridors was 1883.78 km, 982.67 km and 603.09 km, respectively. (3) The crucial areas of territorial ecological restoration were composed of the 37 ecological pinch points, 5 ecological barrier points, 35 urban sources and 62 demand corridors. Targeted restoration of these crucial areas can significantly improve the ecological connectivity. Combined with the land use status and spatial distribution characteristics of crucial areas of territorial ecological restoration, some improvement directions of ecological restoration were put forward. This study provides new ideas for the source identification and the corridor extraction of ESP, and provides a reference for the identification and restoration strategy of crucial areas of territorial ecological restoration.